Prevalence of AGER gene polymorphism in post menopause Iraqi sample with Osteoporosis and osteopenia in type 2DM - Murooj G Jameel; Zainab M Alhakeem; Mohammad H Al-Osami (College of Pharmacy University of Baghdad, 2022)
Osteoporosis (OP)is one of the most important metabolic disorder also affected by interaction of genetic and environmental factors by almost 70% and 30% respectively. Genetic components are identified to strongly effect bone mineral density, bone building and turnover, so they play an important role in determining risk of OP and fragility fractures. This study consists of patient and control group; Group A: (70) postmenopausal women with OP and osteopenia, Group B: (20) control group.  five milliliters of blood sample were divided into three tubes; one tube (1ml) contain gel for obtain serum to measure glucose level, the others tubes containing ethylene-diamine-tetra-acetic acid (EDTA), in 2 tube 2ml stored in deep freeze at (-40 Co) until genomic analysis of DNA for the performance of PCR genotyping of gene polymorphisms of RAGE, in 3 tube 2ml used to perform Glycated Hemoglobin % (HbA1c) assays. HbA1c and Serum glucose levels is significantly increased in Group A. a high prevalence of RAGE polymorphism rs1800625 and rs1800624 were detected in postmenopausal women with OP with type2DM. Homozygous 1800625 were (31%) and heterozygous 1800625(31%) compared to control homozygous 1800625 were (5%) and heterozygous 1800625 were (5%) respectively. Homozygous 1800624 were (28.5%) and heterozygous 1800624(28.5%) compared to control homozygous 1800624 were (5%) and heterozygous 1800624 were (20%) respectively. In conclusion, the rs1800625 and rs1800624 polymorphism might be a causal risk allele for OP in post menopause Iraqi women with type2 DM.